Perlindungan Hukum Konsumen Akibat Wanprestasi Jumlah Barang Dalam Transaksi Jual Beli Online : Studi Putusan Nomor 629/Pdt.G/2020/PN JKT.SEL - Jihan Asyfa Viradrian; Suraji Suraji (Indonesian Publication Center, 2026)
This study examines the juridical qualification of breach of contract involving quantity discrepancies in online sales transactions and the effectiveness of consumer legal protection mechanisms, with a case study on Decision No. 629/Pdt.G/2020/PN JKT.SEL (Namastudio Case). A normative prescriptive legal method is applied using the statute and case approaches. The findings indicate that quantity discrepancies constitute imperfect performance under Article 1243 of the Civil Code, obliging the seller to provide compensation. Consumer protection may be pursued preventively through government supervision and repressively through the BPSK or general courts. Although the legal framework is adequate, its effectiveness remains hindered by low public legal awareness and weak oversight of digital businesses.